PENGARUH GAME-BASED LEARNING BERBANTUAN GAME EDUKATIF “AYO MENDAUR ULANG” TERHADAP KREATIVITAS SISWA SEKOLAH DASAR - Dista Olivia Efranji; Sholikhan, Sholikhan; Arnelia Dwi Yasa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary school learning is generally still oriented toward mastery of subject matter, so students’ creativity has not been fully facilitated. Therefore, a learning strategy is needed that can create an active and enjoyable learning process while Giving pupils the chance to freely share their thoughts. The purpose of this study is to investigate how primary school students' creativity is affected when the game-based learning approach is used in conjunction with the educational game